A Voronovskaya type theorem for q-Szász-Mirakyan-Kantorovich operators - Başcanbaz-Tunca, Gülen; Erençin, Ayçegül (Rev. Anal. Numér. Théor. Approx., 2011)
In this work, we consider a Kantorovich type generalization of \(q\)-Szász-Mirakyan operators via Riemann type \(q\)-integral and prove a Voronovskaya type theorem by using suitable machinery of \(q\)-calculus.